IDENTIFIKASI JENIS DAN SEBARAN BAMBU DI KELURAHAN TUBO KOTA TERNATE UTARA - Nurhikmah; Musa, Nurila Hi; Tamrin, Mahdi (Prodi Kehutanan Universitas Khairun, 2025)
Research on Identification of Bamboo Types and Distribution in Tubo Village, North Ternate City the aim of knowing the types and distribution of bamboo in Tubo village. The research method used in this study is the transek method with purposive sampling technique, which is exploring plantations in Tubo Village that have been identified as having bamboo species. Research data were analyzed descriptively in the form of tables and figures. Data that has been collected in the field is then explained or described in sentence form. The results showed that in Tubo Village, North Ternate City, 4 (four) types of bamboo were found consisting of 4 (four) different genus namely Gigantochloa, Dendrocalamus, Bambusa, and Schziostachyum. Of the types of bamboo found come from the Poaceae family. The distribution pattern of bamboo plants in Tubo Village is irregular (Random) this can be seen from the difference in the distance where bamboo plant species grow with the river body The pattern of bamboo distribution is depicted in a distribution map by photographing to find out the coordinate points using a camera times camp at the location where bamboo is found. Keywords: Identification, Bamboo, spread pattern.